Nosocomial Pathogens: An In-Depth Analysis of the Vectorial Potential of Cockroaches - Eric S. Donkor (Tropical Medicine and Infectious Disease, 2019)
Nosocomial or healthcare-associated infections are regarded as the most frequent adverse event that threatens patients’ safety and has serious economic and social consequences. Cockroach infestation is common in many hospitals, especially in the developing world. Common nosocomial pathogens isolated from cockroaches include Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Klebsiella pneumoniae. Cockroaches also harbor epidemiologically significant antibiotic-resistant organisms, such as carbapenem-resistant Enterobacteriaceae, which complicate nosocomial infections. Therefore, cockroaches constitute an important vector for nosocomial pathogens, and there should be zero tolerance for their presence in healthcare facilities. This paper aims to elucidate the possible role of cockroaches in nosocomial infections by reviewing the relevant research publications.